MANAJEMEN PENDIDIKAN DEMOKRASI DALAM MEMBINA PERILAKU KEBHINEKAAN PADA PONDOK PESANTREN - Taupik Rohmansyah; Heru Sujiarto; Hanafiah Hanafiah; Ahmad Khori (Balai Diklat Keagamaan Bandung, 2022)
Boarding school’s acceptance of new things while retaining the old things on good terms (ashlah) allows the boarding to survive and align with existing developments and deconstructs new values using the yellow book as a reference, including state, social politics, human rights, sociocultural diversity, and democracy responses. This study employs a qualitative approach with descriptive methodologies: observation, interviews, and documentation for data gathering, and focuses on management theory. The results demonstrated that each level of management is properly implemented. Furthermore, the term democratic education is not explicitly stated in the curriculum of boarding education; however, the spirit, values, ideas, perceptions, and practices of democracy manifested in daily life, such as the building of the spirit of cooperation in the student’s learning process, appreciation for fellow students and teachers, cleric and kyai, as well as the election of chairman regularly. The curriculum, which is considered to hidden, is firmly stated as numerous characteristics of the boarding school outside the studied ones, such as organizational aspects, social, and cultural systems, yet it is able to affect changes in students' values, perceptions, and actions.Keywords: Management; Democratic Education; Diversity Behavior